Mediating role of gender on the impact of human resource strategies on knowledge-based employees: a study on human strategies affecting organizational health - Hasani Ahmadiyeh , Sedigheh; Manzari Tavakoli, Alireza; Salajegheh , Sanjar; Fatehi Rad, Navid (Social Determinants of Health, 2022)
Background: Rapid growth of the organization depends on capable and efficient human resources that provide the conditions for producing more diverse, better, and more products in global markets by using any technology. Methods: The present study was applied-developmental in terms of purpose and descriptive-correlational method. All 86750 employees of public organizations in Kerman province in 2019 were considered the study's statistical population. Using Cochran's formula, the sample size was estimated at 384 people. The selection was done by the stratified sampling method. Data collection included a 98-item questionnaire of knowledge-based staff with a 0.87 validity and a 0.74 reliability and a 50-item questionnaire of human resources strategies with a 0.85 validity and a 0.87 reliability. Data analysis was performed using Amos and SPSS software. Results: The results revealed a significant difference effect of secondary, a free agent, committed strategies on knowledge-based employees in public organizations in Kerman province considering the mediating role of gender. However, the effect of paternalistic strategy on knowledge-based employees in Kerman public organizations considering the mediating role of gender was not significant. Conclusion: Managers and policymakers could apply the findings of this study in determining the position and level of employees as designers and key actors of the organization and in the appointment, recruitment, retention and evaluation system.